Islamic Perspectives on Basic Income - Katherine Bullock (International Institute of Islamic Thought, 2019)
The aim of this research is to present the Islamic perspective on the concept of Basic Income, and examine its emergence with the first Islamic society established at the time of Prophet Mohammad (pbuh). The scope of this research is to provide a historical account of Islamic society’s and Qur’anic foundations of social justice, provide Islamic definitions of the concepts involved in the Basic Income debate (such as wealth, poverty, and work), and discuss the Islamic approach to Basic Income. Finally, the research will consider Islamic perspectives on the role of charity and the use of natural resources as sources of revenue to fund Basic Income.